Updating Fragility Curves for Portuguese Pre-Seismic Code Reinforced Concrete Buildings - Moghimi, Sanam (2019)
This paper is part of a broader study under development at LNEC with the main aim of defining general policies for the cost-effective seismic retrofitting of the existing Portuguese building stock. The paper will summarise the methodology implemented for determining accurate capacity and fragility curves of existing pre-seismic design code reinforced concrete (RC) buildings when subjected to seismic action. The methodology involved the definition of probabilistic models of relevant input variables (geometry and materials), performing advanced numerical models of RC buildings under seismic action, setting of appropriate limit states and finally analysis of the results in order to derive the updated curves for Portuguese building stock. This paper will also present a comparison between curves obtained from the current study and the corresponding curves currently being used in LNEC’s seismic risk assessment platform (LNECloss).